Molecular characterization and organic acid production of mineral phosphate solubilizing bacteria for Malaysian soil - Matthews, Stella (2012)
The present study emphasizes on the isolation and characterization of bacteria with the ability to solubilize mineral phosphates based on the consistency to form clear zone on National Botanical Research Institute’s Phosphate Growth Medium agar medium (NBRIP) and the ability to release high amount of orthophosphates from insoluble mineral phosphates. Ten bacteria were identified as efficient mineral phosphate solubilizers namely 7 strains of Klebsiella pneumoniae, 2 strains of Enterobacter aerogenes and 1 strain of Pseudomonas aeruginosa. All the ten strains were able to dissolve calcium phosphate (Ca-P), ferric phosphate (Fe-P) and aluminium phosphate (Al-P) efficiently. Ca-P solubilization and the time of incubation were well correlated (correlation = 0.708, p = 0.000). The best Ca-P solubilizer was STMPSB 8 (Klebsiella penumoniae) which could solubilize 1772.5±112.4 mg/L orthophosphate. The best Fe-P solubilizer was STMPSB 9 (Klebsiella pneumoniae) which could release 1679.11±8.43 mg/L of orthophosphate. The best Al-P solubilizer was STMPSB 8 which has recorded 1198.57±14.04 mg/L of orthophosphate release. STMPSB 8 (Klebsiella pneumoniae) could be designated as the best mineral P solubilizer for all the three insoluble mineral phosphates as it has exhibited high solubilization capacity for Ca-P, Fe-P and Al-P. Consequently, multiple organic acids such as gluconic acid, 2- ketogluconic acid, malic acid, pyruvic acid, acetic acid, propoanoic acid, glutaric acid, lactic acid, succinic acid, citric acid and fumaric acid were detected by Gas Chromatograph–Mass Spectrometer (GC-MS) which could have contributed to the solubilization of mineral phosphates. These organic acids may also function as chelators and involve in biocontrol activity as well. Phytohormones such as indole acetic acid (IAA) and gibberellic acid were also detected in some bacteria. High Performance Liquid Chromatography (HPLC) analysis was able to quantify gluconic acid and 2-ketogluconic acid produced by these bacterial strains. Gluconic acid was detected in all the bacterial isolates but 2-ketogluconic acid was only detected in seven of them. The correlation between gluconic acid production and solubilization of mineral phosphates was 0.795, significant at the 0.01 level. The highest amount of gluconic acid was produced by STMPSB 6 (199.51±36.56 mg/ml) followed by STMPSB 4 (197.04±24.67 mg/ml) where both strains were Enterobacter aerogenes. Finally, the detection of pqq C gene in eight of the bacterial isolates indicates that direct oxidation pathway was used during biosynthesis of gluconic acid with the aid of PQQ cofactor. Partial sequences of the pqq C gene obtained in the present study were deposited in the GenBank. The accession numbers were JF683614, HQ727983, JF683615, JF683626, JF683617, HQ727985, JF683613 and JF683618. Based on this study it was concluded that the majority of the Gram negative bacteria produce multiple organic acids particularly gluconic acid to facilitate the mineral phosphate solubilization. These strains could be explored further for the production of biofertilizer.